Analisis Kompetensi Guru dan Ketersediaan Sarana Prasarana sebagai Pendukung Pembelajaran Musik di Sekolah Dasar - Pratiwi, Andita; Thursina, Aldavia; Ananda Gusti, Chintia; An Najmi, Meyra; Herdiana Putri, Sherina; Ginanjar Rahayu, Teten (STKIP Subang, 2026)
This study aims to analyze teacher competence and the availability of facilities and infrastructure as supporting factors in music learning at elementary schools. The study employed a Systematic Literature Review (SLR) method based on the PRISMA guidelines. The literature search process was conducted through the Google Scholar database using the Publish or Perish application, covering publications from 2020 to 2025. Based on the selection process, 26 articles that met the inclusion criteria were obtained and analyzed using a qualitative descriptive approach. The results indicate that teacher competence and the availability of facilities and infrastructure play an important role in the success of music learning in elementary schools. The main challenges identified include limited teacher professional competence, lack of mastery of music teaching methods, and insufficient facilities such as musical instruments, learning media, and supporting technology. On the other hand, the use of digital media, simple musical instruments, and creative learning approaches has proven effective in improving students’ motivation, creativity, and musical skills. In addition, proper management of facilities and infrastructure also supports the creation of more effective and enjoyable music learning. Therefore, improving the quality of music learning requires strengthening teacher competence and providing adequate facilities and infrastructure so that the learning process can run optimally